Satellite-Like W-Elements: Repetitive, Transcribed, and Putative Mobile Genetic Factors with Potential Roles for Biology and Evolution of Schistosoma mansoni. (1st September 2021) - Stitz, Maria; Chaparro, Cristian; Lu, Zhigang; Olzog, V Janett; Weinberg, Christina E; Blom, Jochen; Goesmann, Alexander; Grunau, Christoph; Grevelding, Christoph G
Abstract: A large portion of animal and plant genomes consists of noncoding DNA. This part includes tandemly repeated sequences and gained attention because it offers exciting insights into genome biology. We investigated satellite-DNA elements of the platyhelminth Schistosoma mansoni, a parasite with remarkable biological features. Schistosoma mansoni lives in the vasculature of humans causing schistosomiasis, a disease of worldwide importance. Schistosomes are the only trematodes that have evolved separate sexes, and the sexual maturation of the female depends on constant pairing with the male. The schistosome karyotype comprises eight chromosome pairs, males are homogametic (ZZ) and females are heterogametic (ZW). Part of the repetitive DNA of S. mansoni are W-elements (WEs), originally discovered as female-specific satellite DNAs in the heterochromatic block of the W-chromosome. Based on new genome and transcriptome data, we performed a reanalysis of the W-element families (WEFs). Besides a new classification of 19 WEFs, we provide first evidence for stage-, sex-, pairing-, gonad-, and strain-specific/preferential transcription of WEs as well as their mobile nature, deduced from autosomal copies of full-length and partial WEs. Structural analyses suggested roles as sources of noncoding RNA-like hammerhead ribozymes, for which we obtained functional evidence. Finally, the variable WEF occurrence in different schistosome species revealed remarkable divergence. From these results, we propose that WEs potentially exert enduring influence on the biology of S. mansoni . Their variable occurrence in different strains, isolates, and species suggests that schistosome WEs may represent genetic factors taking effect on variability and evolution of the family Schistosomatidae.